Ecological security pattern construction based on landscape ecological risk assessment in the Yellow River basin - Yan, Jixuan; Li, Jie; Yao, Xiangdong; Li, Qiang; Zheng, Zhiqin; Li, Guang; Qi, Guangping; Ma, Weiwei; Song, Miao; Gao, Pengcheng (Frontiers in Environmental Science, 2025)
The Yellow River Basin is one of the most ecologically fragile zones in China. Landscape ecological risk assessment and ecological security pattern construction are effective ways to find out and solve the problems of the ecological environment in this region. In this study, based on LUCC and driving factor data, we evaluated the spatial distribution characteristics of landscape ecological risk from the grid scale using the ecological risk index (ERI) and minimum cumulative resistance (MCR) models, especially proposing a new method for constructing the ecological security pattern from the perspective of landscape ecological risk assessment and finally forming an ecological security pattern network composed of points, lines, and surfaces. The results indicated that the ecological risk of the Yellow River basin showed a spatial distribution pattern of “High in southwest and northwest, low in other regions.” The middle–low level ecological risk accounted for more than 86% of the total area. The study has formed an ecological security pattern network consisting of 12 core ecological sources, 92 ecological nodes, 12 key corridors, 16 auxiliary corridors, and 4 different controlled areas. According to these study findings, we provide ecological protection strategies that strengthen the ecological source conservation, attaching importance to the construction of ecological corridor, increasing the restoration of ecological nodes, and carrying out the zoning regulation. This study will provide a new insight for the construction of the ecological security pattern network based on the results of landscape ecological risk assessment.